Step
*
1
of Lemma
strong-continuity2-implies-3
1. [T] : Type
2. [F] : (ℕ ⟶ T) ⟶ ℕ
3. M : n:ℕ ⟶ (ℕn ⟶ T) ⟶ (ℕ?)
4. ∀f:ℕ ⟶ T. ((∃n:ℕ. ((M n f) = (inl (F f)) ∈ (ℕ?))) ∧ (∀n:ℕ. (M n f) = (inl (F f)) ∈ (ℕ?) supposing ↑isl(M n f)))
⊢ ∃M:n:ℕ ⟶ (ℕn ⟶ T) ⟶ (ℕ?)
   ∀f:ℕ ⟶ T. ∃n:ℕ. (((M n f) = (inl (F f)) ∈ (ℕ?)) ∧ (∀m:ℕ. ((↑isl(M m f)) 
⇒ (m = n ∈ ℕ))))
BY
{ (InstConcl [⌜λn,f. strong-continuity-test(M;n;f;M n f)⌝]⋅ THEN Try (CpltAuto)) }
1
1. [T] : Type
2. [F] : (ℕ ⟶ T) ⟶ ℕ
3. M : n:ℕ ⟶ (ℕn ⟶ T) ⟶ (ℕ?)
4. ∀f:ℕ ⟶ T. ((∃n:ℕ. ((M n f) = (inl (F f)) ∈ (ℕ?))) ∧ (∀n:ℕ. (M n f) = (inl (F f)) ∈ (ℕ?) supposing ↑isl(M n f)))
⊢ ∀f:ℕ ⟶ T
    ∃n:ℕ
     ((((λn,f. strong-continuity-test(M;n;f;M n f)) n f) = (inl (F f)) ∈ (ℕ?))
     ∧ (∀m:ℕ. ((↑isl((λn,f. strong-continuity-test(M;n;f;M n f)) m f)) 
⇒ (m = n ∈ ℕ))))
Latex:
Latex:
1.  [T]  :  Type
2.  [F]  :  (\mBbbN{}  {}\mrightarrow{}  T)  {}\mrightarrow{}  \mBbbN{}
3.  M  :  n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  T)  {}\mrightarrow{}  (\mBbbN{}?)
4.  \mforall{}f:\mBbbN{}  {}\mrightarrow{}  T
          ((\mexists{}n:\mBbbN{}.  ((M  n  f)  =  (inl  (F  f))))  \mwedge{}  (\mforall{}n:\mBbbN{}.  (M  n  f)  =  (inl  (F  f))  supposing  \muparrow{}isl(M  n  f)))
\mvdash{}  \mexists{}M:n:\mBbbN{}  {}\mrightarrow{}  (\mBbbN{}n  {}\mrightarrow{}  T)  {}\mrightarrow{}  (\mBbbN{}?)
      \mforall{}f:\mBbbN{}  {}\mrightarrow{}  T.  \mexists{}n:\mBbbN{}.  (((M  n  f)  =  (inl  (F  f)))  \mwedge{}  (\mforall{}m:\mBbbN{}.  ((\muparrow{}isl(M  m  f))  {}\mRightarrow{}  (m  =  n))))
By
Latex:
(InstConcl  [\mkleeneopen{}\mlambda{}n,f.  strong-continuity-test(M;n;f;M  n  f)\mkleeneclose{}]\mcdot{}  THEN  Try  (CpltAuto))
Home
Index